Snow White and the seven dwarfs - Sims, Lesley; Guicciardini, Desideria Grimm, Jacob Grimm, Wilhelm (Usborne London, 2005)
Each book in this series is designed to encourage independent reading and covers a range of subject matter, including the retelling of children's classics, fairytales, and a wide variety of narrative non-fiction. This edition retells the Brothers Grimm story of 'Snow White'. Three titles in the popular Young Reading series are re-issued with hardback covers with audio CDs inserted into a wallet inside the back cover, making the book and CD easy to store together. The Young Reading series is developed with reading expert Alison Kelly from Roehampton University to help young readers grow in confidence and ability